Heart Allograft Tolerance Induced and Maintained by Vascularized Hind-Limb Transplant in Rats - Quan Liu; Yong Wang; Atsunori Nakao; Wensheng Zhang; Vijay Gorantla; Xin Xiao Zheng (Clinical and Developmental Immunology)
Organ/tissue transplantation has become an effective therapy for end-stage diseases. However, immunosuppression after transplantation may cause severe side effects. Donor-specific transplant tolerance was proposed to solve this problem. In this study, we report a novel method for inducing and maintaining heart allograft tolerance rats. First, we induced indefinite vascularized hind-limb allograft survival with a short-term antilymphocyte serum + Cyclosporine A treatment. Peripheral blood chimerism disappeared 6-7 weeks after immunosuppression was withdrawn. Then the recipients accepted secondary donor-strain skin and heart transplantation 200 days following vascularized hind-limb transplantation without any immunosuppression, but rejected third party skin allografts, a status of donor-specific tolerance. The ELISPOT results suggested a mechanism of clone deletion. These findings open new perspectives for the role of vascularized hind-limb transplant in the induction and maintenance of organ transplantation tolerance.